Starting the aircraft engines and gas-turbine drive by means of electric starter - Іщенко, І.М.; Гуз, Ю.Т.; Сіткевич, Т.А. (Proceedings of National Aviation University (archive), 2004)
In the article the questions of the starting the aircraft engines and gas-turbine drive by means of electric starter is considered. In the same way in the article are determined the main requirements to steady-state converter for feeding electric starter.